Association of oropharyngeal colostrum administration with decreased inflammatory indices in premature newborns weighing less than 1500 g - Guadalupe Gómez-Rodríguez; Juan L. Moreno-Saldaña; Evaldo J. Rodríguez-Mejía; Marco A. Olvera-Olvera (Permanyer, 2024)
Background: The administration of colostrum through its absorption at the oropharyngeal level stimulates the mucosa-associated lymphoid tissue, providing a local immunological protection barrier. The study aimed to investigate the association of oropharyngeal colostrum administration with the reduction of inflammatory indices. Materials and methods: This was an observational, ambispective, analytical study of newborns < 32 weeks of gestation at risk of sepsis. Oropharyngeal colostrum was administered at 0.2 mL every 4 h for 5 days. Inflammatory indices were analyzed. Statistical analysis included frequencies, percentages, mean and Standard deviation, contingency coefficient, and Kolmogorov-Smirnov test for the distribution curve of the numerical data. Results: There were 50 patients, 33 (66%) female and 17 (34%) male, with a median gestational age of 30-31 weeks (95% confidence interval [CI]). Nineteen patients had sepsis. A lower positivity rate in C-reactive protein was found, with a median of 0.5-0.6 (95% CI) at 5 days of colostrum administration versus 0.5-1.1 (95% CI) as the initial C-reactive protein. Analysis with χ2 yielded a p = 0.13, and the contingency coefficient showed a p = 0.196, indicating an association. Conclusion: Oropharyngeal colostrum administration was associated with a lower C-reactive protein positivity rate and clinical improvement in premature newborns at risk of sepsis.